The Creolisation of London Kinship Mixed African-Caribbean and White British Extended Families, 1950-2003 - Bauer, Elaine (IMISCoe Dissertations, 2010)
In the last 50 years, the United Kingdom has witnessed a growing proportion of mixed African-Caribbean and white British families. With rich new primary evidence of 'mixed-race' in the capital city, The Creolisation of London Kinship thoughtfully explores this population. Making an indelible contribution to both kinship research and wider social debates, the book emphasises a long-term evolution of family relationships across generations. Individuals are followed through changing social and historical contexts, seeking to understand in how far many of these transformations may be interpreted as creolisation. Examined, too, are strategies and innovations in relationship construction, the social constraints put upon them, the special significance of women and children in kinship work and the importance of non-biological as well as biological notions of family relatedness.